1997
DOI: 10.1111/j.1558-5646.1997.tb02435.x
|View full text |Cite
|
Sign up to set email alerts
|

MICROSATELLITES REVEAL HIGH POPULATION VISCOSITY AND LIMITED DISPERSAL IN THE ANTFORMICA PARALUGUBRIS

Abstract: Abstract.-We used micro satellites to study the fine-scale genetic structure of a highly polygynous and largely unicolonial population of the ant Formica paralugubris. Genetic data indicate that long-distance gene flow between established nests is limited and new queens are primarily recruited from within their natal nest. Most matings occur between nestmates and are random at this level. In the center of the study area, budding and permanent connections between nests result in strong population viscosity, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(22 citation statements)
references
References 71 publications
1
20
1
Order By: Relevance
“…Furthermore, we found no strong evidence for isolation by distance among colonies within sites. Other studies of polygynous Formica (Chapuisat et al, 1997;Pirk et al, 2001) and even some weakly polygynous ants (Fournier et al, 2002) have reported correlations of distance and genetic differentiation that were many times larger than the values we found in this system. Thus, F. podzolica shows substantially weaker within-population subdivision than other polygynous or socially polymorphic Formica species.…”
Section: Discussioncontrasting
confidence: 55%
“…Furthermore, we found no strong evidence for isolation by distance among colonies within sites. Other studies of polygynous Formica (Chapuisat et al, 1997;Pirk et al, 2001) and even some weakly polygynous ants (Fournier et al, 2002) have reported correlations of distance and genetic differentiation that were many times larger than the values we found in this system. Thus, F. podzolica shows substantially weaker within-population subdivision than other polygynous or socially polymorphic Formica species.…”
Section: Discussioncontrasting
confidence: 55%
“…This estimator is not bounded between 0 and 1. When the population is structured, relatc adequately removes the increase in relatedness due to this structuring (see Chapuisat et al 1997, for an example).…”
Section: Discussionmentioning
confidence: 99%
“…Colony formation can also occur via budding, (e.g. Chapuisat et al, 1997;Chapuisat and Crozier, 2001) in which workers apparently choose the new nest site. Nest relocations after colony formation are common in some species (Smallwood and Culver, 1979;Smallwood, 1982;Briano et al, 1995;Byrne, 1994;Banschbach and Herbers, 1999), and are thought to be a response to intolerable nest conditions and/or locating a more favorable nest site (Smallwood, 1982;Tinaut et al, 1999).…”
Section: Introductionmentioning
confidence: 99%